2016
DOI: 10.2147/ndt.s111094
|View full text |Cite
|
Sign up to set email alerts
|

Suicidality and symptoms of anxiety, irritability, and agitation in patients experiencing manic episodes with depressive symptoms: a naturalistic study

Abstract: PurposePatients with a bipolar I disorder (BD-I) manic episode meeting the Diagnostic and Statistical Manual of Mental Disorders, fifth edition (DSM-5), criteria for “with mixed features” have a high incidence of suicide attempts and of anxiety, irritability, and agitation (AIA) symptoms. The aim of this analysis was to explore the relationship between suicidality and AIA symptoms in patients with BD-I experiencing mania with depressive symptoms, using data from a previous naturalistic study.Patients and metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…It is notable that participants with AIA, a group known to be at especially high risk of suicide, experienced similar anti-SI effects as participants without AIA. 9,37,38 We did not observe any evidence of treatment-emergent mania or psychosis, nor were there any other notable tolerability or safety concerns in this population.…”
Section: Discussionmentioning
confidence: 58%
“…It is notable that participants with AIA, a group known to be at especially high risk of suicide, experienced similar anti-SI effects as participants without AIA. 9,37,38 We did not observe any evidence of treatment-emergent mania or psychosis, nor were there any other notable tolerability or safety concerns in this population.…”
Section: Discussionmentioning
confidence: 58%
“…This replicates the findings of a naturalistic study, in which anxiety and irritability were more common in BD-I patients with three or more depressive symptoms, whereas agitation was not (Young and Eberhard 2015 ). Thus, anxiety and irritability, and the combination of all three AIA symptoms, could potentially be used as non-specific indicators, or ‘gateway symptoms’, to help psychiatrists identify bipolar mania with depressive symptoms (Eberhard and Weiller 2016 ). At present, the DSM-5 does not highlight or discuss AIA symptoms in the ‘with mixed features’ specifier section.…”
Section: Discussionmentioning
confidence: 99%
“…In BD-I (unlike in MDD) there has been relatively little prior investigation into whether patient characteristics (including AIA) within an episode can affect treatment response and other health outcomes (Feske et al 2000 ). A recent analysis showed that the presence of AIA symptoms raises the already high suicide risk among patients with BD-I mania with depressive symptoms (Eberhard and Weiller 2016 ). Additionally, a subtype of bipolar depression, characterised by anxiety and irritability among other symptoms, is associated with a greater likelihood of receiving government financial support, suggesting that this pattern of symptoms is particularly malignant (Perich et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Depression can be long-lasting or recurrent, substantially impairing not only patients’ quality of life but also of their families. Moreover, depression can also lead to suicide, which is the second leading cause of death in adolescents 3,4. However, the underlying molecular mechanisms of depression remain largely unknown 5…”
Section: Introductionmentioning
confidence: 99%